Effectiveness of Beta Blockers against Hypertrophic Cardiomyopathy - Muhammad Yousaf, Munir Ahmad Khan, Muhammad Tahir, Pir Abdul Hayee, Maleeha Tahir Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the efficacy of beta adrenergic blockers against hypertrophic cardiomyopathy. Study Design: Retrospective study Place and Duration of Study: Khyber Teaching Hospital Peshawar from 1st April 2021 to 30th September 2021. Methodology: All the data was retrieved from the medical files of the patients who were registered as out/indoor patients at cardiology department. The sample size for this study was taken as 110 patients and age was between 5-76 years. Each patient complete information regarding age, gender, clinical history, comorbidity history, clinical symptoms, clinical assessment results, echo and ECG results was documented on a well-structured questionnaire. Patients were given beta blockers for two-year time and the effectiveness of various beta blockers was recorded. Results: There were 57.27% males while 42.73% were females. Patients where increased left ventricle outflow-tract such as LVOT was observed the efficiency of beta blocker was significantly reduced. A value of LVOT ≥50mmHg was presented in patients of the later ages while LVOT <50mmHg was seen in young and pediatric cases. Conclusion: Beta adrenergic blockers showed great effectiveness against hypertrophy cardiomyopathy.